Uniqueness of L-Functions Concerning Certain Differential Polynomials - Wen-Jie Hao; Jun-Fan Chen (Discrete Dynamics in Nature and Society)
Relying on Nevanlinna theory and the properties of L-functions in the extended Selberg class, we mainly study the uniqueness problems on L-functions concerning certain differential polynomials. This generalizes some results of Steuding, Li, Fang, and Liu-Li-Yi.